Atrial myxoma presenting as a cerebellar stroke - Azhar AH,; Ziyadi G,; Zulkarnain H,; Rahman MNG, (Department of Surgery, UKM Medical Centre, 2011)
Primary tumors of the heart are rare. However, among them cardiac myxoma is the most common tumor accounting for half of the primary cardiac neoplasms. About 75% of cardiac myxomas are located in the left atrium, and 25% are located in the right atrium. These are thought to be arising from remnants of subendocardial vasoformative reserve cells or multipotential primitive mesenchymal cells in the fossa ovalis and surrounding endocardium, which can differentiate along a variety of cell lineages including epithelial, hematopoietic, and muscle cells. Although some cases are discovered incidentally by echocardiographic examination, it was recognized in most of the patients by various symptoms caused by the release of inflammatory cytokines such as interleukin-6 (IL-6), obstruction of intracardiac blood flow, or embolization. Cardiac myxoma has many undetermined interesting issues regarding its origin, nature as a tumor, varying clinical manifestations, and the presence of both sporadic and familial types. Recent evidence revealed that cardiac myxomas are benign neoplasms and slowly proliferating lesions. The existence of its malignant counterpart is controversial. However, recurrence after surgical excision or metastasis has been reported. We hereby present a case report of a young gentleman who presented with history of sudden onset of weakness and cerebellar signs. Urgent CT scan revealed hypodensities of bilateral occipital lobes and cerebellum suggestive of infarcts. Urgent echocardiography denoted large left atrial myxoma. The tumor was excised and the patient recovered well.